2024
DOI: 10.3390/ma17071485
|View full text |Cite
|
Sign up to set email alerts
|

Improved Bending Strength and Thermal Conductivity of Diamond/Al Composites with Ti Coating Fabricated by Liquid–Solid Separation Method

Hongyu Zhou,
Qijin Jia,
Jing Sun
et al.

Abstract: In response to the rapid development of high-performance electronic devices, diamond/Al composites with high thermal conductivity (TC) have been considered as the latest generation of thermal management materials. This study involved the fabrication of diamond/Al composites reinforced with Ti-coated diamond particles using a liquid–solid separation (LSS) method. The interfacial characteristics of composites both without and with Ti coatings were evaluated using SEM, XRD, and EMPA. The results show that the LSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…It was observed that higher model accuracy could be achieved in samples with a larger cladding layer thickness. Meanwhile, Zhou et al [ 12 ] employed their independently designed liquid–solid separation method to fabricate diamond/Al composites reinforced with 40 vol.% diamond particles, achieving high thermal conductivity. This innovative approach demonstrates the potential for producing composites with superior thermal properties for advanced industrial applications.…”
Section: Contributionsmentioning
confidence: 99%
“…It was observed that higher model accuracy could be achieved in samples with a larger cladding layer thickness. Meanwhile, Zhou et al [ 12 ] employed their independently designed liquid–solid separation method to fabricate diamond/Al composites reinforced with 40 vol.% diamond particles, achieving high thermal conductivity. This innovative approach demonstrates the potential for producing composites with superior thermal properties for advanced industrial applications.…”
Section: Contributionsmentioning
confidence: 99%